Neural Substrates of Homing Pigeon Spatial Navigation: Results From Electrophysiology Studies - Hough, Gerald E. (Frontiers in Psychology, 2022)
Over many centuries, the homing pigeon has been selectively bred for returning to a home location from a distant location. As a result of this strong selective pressure, homing pigeons have developed an excellent spatial navigation system. This system passes through the hippocampal formation, which shares many striking similarities to the mammalian hippocampus; there are a host of shared neuropeptides, interconnections, and its role in the storage and manipulation of spatial maps. There are some notable differences as well: there are unique connectivity patterns and spatial encoding strategies. This review summarizes the comparisons between the avian and mammalian hippocampal systems, and the responses of single neurons in several general categories: 1) location and place cells responding in specific areas, 2) path and goal cells responding between goal locations, 3) context-dependent cells that respond before or during a task, and 4) pattern, grid, and boundary cells that increase firing at stable intervals. Head-direction cells, responding to a specific compass direction, are found in mammals and other birds but not to date in pigeons. By studying an animal that evolved under significant adaptive pressure to quickly develop a complex and efficient spatial memory system, we may better understand the comparative neurology of neurospatial systems, and plot new and potentially fruitful avenues of comparative research in the future.